2016
DOI: 10.3390/nu8020104
|View full text |Cite
|
Sign up to set email alerts
|

Cysteic Acid in Dietary Keratin is Metabolized to Glutathione and Liver Taurine in a Rat Model of Human Digestion

Abstract: Poultry feathers, consisting largely of keratin, are a low-value product of the poultry industry. The safety and digestibility of a dietary protein produced from keratin (KER) was compared to a cysteine-supplemented casein-based diet in a growing rat model for four weeks. KER proved to be an effective substitute for casein at 50% of the total dietary protein, with no changes in the rats’ food intake, weight gain, organ weight, bone mineral density, white blood cell counts, liver glutathione, or blood glutathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 44 publications
2
22
1
Order By: Relevance
“…Specifically, supplementation with thiol-donors such as N-acetyl cysteine (NAC), whose ability to attenuate reduction of glutathione may prevent systemic oxidative stress and hence increase performance-related parameters such as power output and time-to-exhaustion in athletes [ 92 , 93 ], but possibly without preventing the original local stimulus which initiates redox-sensitive cell signalling responses. Accordingly, given that in some individuals oral or systemic administration of NAC can be poorly tolerated [ 2 ], alternative dietary sources of thiols such as taurine and hydrolysed keratin have been recommended [ 2 , 112 ]. However, it should be noted that in another study, NAC supplementation did conform to the hormesis principle by attenuating early adaptive responses to exercise in human skeletal muscle [ 88 ].…”
Section: Exercise-associated Redox-sensitive Signaling Responses Amentioning
confidence: 99%
“…Specifically, supplementation with thiol-donors such as N-acetyl cysteine (NAC), whose ability to attenuate reduction of glutathione may prevent systemic oxidative stress and hence increase performance-related parameters such as power output and time-to-exhaustion in athletes [ 92 , 93 ], but possibly without preventing the original local stimulus which initiates redox-sensitive cell signalling responses. Accordingly, given that in some individuals oral or systemic administration of NAC can be poorly tolerated [ 2 ], alternative dietary sources of thiols such as taurine and hydrolysed keratin have been recommended [ 2 , 112 ]. However, it should be noted that in another study, NAC supplementation did conform to the hormesis principle by attenuating early adaptive responses to exercise in human skeletal muscle [ 88 ].…”
Section: Exercise-associated Redox-sensitive Signaling Responses Amentioning
confidence: 99%
“…Without prior published work it is difficult to provide a comparison. However a preceding rodent study [ 9 ] comparing CAS and KER supplementation suggested that KER may promote LM gain, although the results did not reach significance. There is an earlier published report that increasing the sulfur amino acid content (specifically CYS and methionine) above a CAS-based diet, in rodents at least, maximises weight gain [ 21 ].…”
Section: Discussionmentioning
confidence: 92%
“…The study used a randomized, blinded, balanced crossover design, with two four-week intervention periods (INT1: intervention 1; INT2: intervention 2) involving supplementation with either KER or a low-cysteine protein (“gold standard” sodium caseinate, CAS [ 9 ]). The interventions were separated by a minimum of 8 weeks to allow wash-out of any remaining traces of the supplement from the participant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations